1997
DOI: 10.1111/j.1399-3054.1997.tb03053.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐induced abscisic acid transients and stimulus‐response‐coupling

Abstract: 1997, Stress-mduced abicisic acid transients and siimulus-response-coupling. -Physiol. Pianl. !(X): 491^99,Loss of cell turgttr and distortion of the plasma membrane occur a.s a result of dehydration and precede tbe stress-induced bulk increase in concentration of tissue abscisic acid. The latter ha-, been correlated v.iih induction of stress-related gene expression. However, several different stresses may trigger the same coupling mechanism. Thus, al least ibree signalling pathways have been proposed: abscisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…These SA Ca 21 -permeable channels may, at least in part, account for the osmo-sensitive macroscopic Ca 21 currents across the PM of guard cells and serve as an osmotic-sensing target in a negative feedback loop. This negative feedback loop, together with the positive feedback loop proposed previously (Liu and Luan, 1998), may explain the mechanisms for osmo regulation of stomatal movements and oscillation (Cowan et al, 1997).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…These SA Ca 21 -permeable channels may, at least in part, account for the osmo-sensitive macroscopic Ca 21 currents across the PM of guard cells and serve as an osmotic-sensing target in a negative feedback loop. This negative feedback loop, together with the positive feedback loop proposed previously (Liu and Luan, 1998), may explain the mechanisms for osmo regulation of stomatal movements and oscillation (Cowan et al, 1997).…”
mentioning
confidence: 52%
“…Therefore, SA Ca 21 channels may be also actively functioning during stomatal closure. The possible complex interaction between the positive and negative feedback mechanisms by which a number of ion transporters are regulated may explain stomatal oscillation under variable environmental conditions (Cowan et al, 1997). Liu and Luan (1998) reported that hypotonic or hypertonic condition caused gradual swelling or Figure 8.…”
Section: Potential Roles Of the Osmo-regulated Ca 21 Channels In Regumentioning
confidence: 99%
“…ABA could (Goh et al 1996;Zhang et al 2004). It is well known that ABA level increases when plants are stressed with NaCl (Cowan et al 1997;Barkla et al 1999). According to the above studies, the decrease in PM H + -ATPase activity by NaCl treatment might be caused by ABA production to reduce the protein phosphorylation.…”
Section: Discussionmentioning
confidence: 96%
“…4 show that there was no difference in the ability of wildtype and P SAG12 -IPT plants to accumulate ABA in response to a water-eficit stress. In both, ABA accumulation commenced 4 day after imposition of stress, reached a maximum within 10 day and then declined, presumably due to ABA-induced ABA catabolism (Cowan et al 1997). Typically, leaves from the apical and middle regions of the canopy produced more ABA than older basal leaves (Fig.…”
Section: Stress-induced and Age-related Changes In Leaf Gas Exchange mentioning
confidence: 98%